2013
DOI: 10.5114/pwki.2013.35459
|View full text |Cite
|
Sign up to set email alerts
|

Stent entrapment and guide wire fracture during percutaneous coronary intervention in the same patient

Abstract: In the performance of increasingly complex PCI there remains an ever-present risk of stent entrapment and guide wire or other device fracture. We report the first case with stent dislodgement and guide wire fracture to occur simultaneously in the same patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The most simple and most commonly used is low-profile balloon inflation up to 4-6 atmospheres within an unexpanded stent or distally to the lost stent 10 . Deployment of other techniques depend on operators experience and skills as well as locally available equipment, and it may include the use of myocardial biopsy or biliary forceps, two twisted guide wires, basket devices, loop snares and other devices 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The most simple and most commonly used is low-profile balloon inflation up to 4-6 atmospheres within an unexpanded stent or distally to the lost stent 10 . Deployment of other techniques depend on operators experience and skills as well as locally available equipment, and it may include the use of myocardial biopsy or biliary forceps, two twisted guide wires, basket devices, loop snares and other devices 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Iatrogenic injuries have accompanied percutaneous coronary intervention (PCI) since the beginning of this modality [1]. In the context of increasing number of complex percutaneous coronary interventions (PCI), dislodgement of an unexpanded coronary stent is a complication that, although rare, still happens [2]. The incidence of lost stent or other devices has dropped from 8.3% to 0.21% due to improvements in the equipment used [[3], [4], [5]].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of lost stent or other devices has dropped from 8.3% to 0.21% due to improvements in the equipment used [[3], [4], [5]]. However, when it happens, it is a serious complication that holds a risk of coronary or systemic thromboembolization, need for emergency coronary artery bypass surgery (CABG), or even death [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…2 Predisposing factors include vessel tortuosity, severe vessel calcification, and a long stent. 3 There are rare case reports in which TEE is used as a diagnostic technique for visualizing entrapped angioplasty devices and helped in decision-making for managing this complication. 4 The presented case highlights the valuable informative role of…”
mentioning
confidence: 99%
“…Previous studies reported a necessity of surgery in 75% of cases . Predisposing factors include vessel tortuosity, severe vessel calcification, and a long stent . There are rare case reports in which TEE is used as a diagnostic technique for visualizing entrapped angioplasty devices and helped in decision‐making for managing this complication .…”
mentioning
confidence: 99%